HATI SUHITA: BETWEEN PESANTREN TRADITION AND JAVANESE PHILISOPHY (IMMANUEL KAHN’S MORAL VALUE ANALYSIS) - Ashfiya, Za’imatil; Mohammad, Che Adenan (Jurnal ’Ulwan, 2025)
This research examines the message implied by the novel Hati Suhita. A novel work born from pesantren about pesantren for Indonesia. This research uses the content analysis method. By referring to this method, researcher tries to understand the contents of the novel Hati Suhita so that the research can capture the implied message of the novel. Khilma Anis’s work combines between pesantren trditions and puppet characters that are full of meaning. The figure of a santri who has the characteristics of a tawadlu’ human being is very nicely depicted in the figure of Alina Suhita. The story of arranged marriages that are widely practiced in pesantren circle is explored in such a way. The slogan mikul duwur mendem jero, which is the mission of this novel, provides a message about how a wife described in Suhita must be able to raise the dignity of the family and must cover all family disgraces. The message should be interpreted broadly as an invitation to be able to respect parent in a narrow sense and elders, teachers, and leaders in a broader sense, and be able to cover the disgrace of other, so that there is peace, considering the many upheavals caused by the number of people who expose the disgrace of others, especially on social media. The invitation to apply the slogan mikul duwur mendem jero is expected to bring change in the midst of the hot phenomenon of indulgence in social media.